Quantitative Analysis of Color Combination from LED and Laser Light Sources Using Modified CIE 1931 Color Space Coordinates - Isnaeni, Isnaeni; Sugiarto, Iyon Titok (Journal of Mathematical and Fundamental Sciences, 2017)
In this study, a quantitative analysis based on the color space coordinates CIE 1931 to determine the color combination from three LEDs (light emitting diode) sources and three laser sources separately, has been investigated. The light sources used in this research were three LEDs that emit blue light, green and red colors, and three laser sources that also emit blue light, green and red colors. Result of color combination from LEDs and laser light sources were detected using a spectrophotometer. The result of the light spectra were then analyzed using a set of color matching function that has been modified specially for the spectrophotometer used. This research produced quantitative analysis for 26 color combinations of LED light sources and 7 color combinations of laser light sources. The results of colors combination were ranging from blue, cyan, yellow, orange, red to purple. Further development is still required to obtain reliable quantitative analysis results.